(untitled) (Eurasian Research Bulletin, 2022)
Postoperative analgesia based on regional blockade of the lumbar plexus (0.1% solutions of naropine or marcaine) and the planned administration of NSAIDs (diclofenac, ketonal or xefocam) is a more effective method of analgesia after surgery in trauma patients of elderly and senile age. The use of low-concentration solutions of local anesthetics (0.1% naropin solution and 0.1% marcaine solution) makes it possible to obtain a complete sensory and minimal motor block, which contributes to the early activation of elderly and senile patients.